منهج العربية في التعبير عن العدد = Manhaj al-'Arabiyah fi al-ta'bir 'an al-'adad - Tingari, Salih (International Islamic University Press, 2013)
This study has attempted to bring to light the modes of expressing numbers in the Arabic language by applying a descriptive and inductive method. It has shown the deep-rootedness among ancient Arabs of the sequence of the singular (mufrad), the dual (muthannÉ) and the plural (jam') in its different kinds. An aspect of the richness of the Arabic language is to express the plural by the singular and assigning the dual a middle position between the singular and the plural, though the dual may also denote the singular. It has also been shown that one common feature between the plural and the dual is to combine and conjoin, yet it differs from it in terms of quantity. The plural has two forms: sound plural and broken plural. Of the findings arrived at in this study is the soundness of classical categorization nouns into singular, dual and plural and the suitability of the plural (together with its varieties) for both fewness and multitude according to the context. The use of fewness plural in place of multitude plural and vice-versa is a matter of allegory.